Icelandic athetes experiences of Olympic Games as a career transition - Sigurgeirsdóttir, R. B. (University of Halmstad, 2013)
The aim of this study was to examine Icelandic elite athletes` experiences in regard to the Olympic Games (OG)-2012. More specifically the focus was on the OG as a career transition process covering several phases in the Olympic cycle, having the Games as its culmination and followed by a career change. The athletic career transition model, the holistic lifespan perspective and temporal structure of the Olympic cycle guided retrospective interviews with six Icelandic athletes who (some years ago) were candidates to take part in the OG-2012. Among the six participants three were successful in the OG-2012, one was less successful and two participants prepared but were not qualified for the OG. Holistic-content and categorical content analyses resulted in: (a) six core narratives describing and interpreting each athlete`s individual pathway through preliminary/basic preparation, selection process, Olympic season, the Games, and post-Games periods, and (b) sixteen themes following athletes` major foci in each transition phase (e.g., "gaining international experience" and "getting financial support" in the preliminary/basic preparation, etc.) and also the transition resources perceived by athletes as necessary during the whole Olympic cycle ("prioritizing sports while balancing sport with work/school", "organizational support" and "family support"). Results are discussed in relation to the theoretical frameworks, previous research, and Icelandic context.